2011
DOI: 10.1128/aem.02972-10
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium glutamicum Tailored for Efficient Isobutanol Production

Abstract: We recently engineered Corynebacterium glutamicum for aerobic production of 2-ketoisovalerate by inactivation of the pyruvate dehydrogenase complex, pyruvate:quinone oxidoreductase, transaminase B, and additional overexpression of the ilvBNCD genes, encoding acetohydroxyacid synthase, acetohydroxyacid isomeroreductase, and dihydroxyacid dehydratase. Based on this strain, we engineered C. glutamicum for the production of isobutanol from glucose under oxygen deprivation conditions by inactivation of L-lactate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
209
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(216 citation statements)
references
References 51 publications
4
209
0
3
Order By: Relevance
“…However, C. glutamicum, which is used for production of amino acids, organic acids and alcohols, does not harbor transhydrogenase genes. Recently, the introduction of transhydrogenase genes into C. glutamicum cells has been examined in an attempt to improve production of amino acids and alcohol (Bartek et al, 2011;Blombach et al, 2011;Kabus et al, 2007). However, the effect of transhydrogenases on cellular metabolism in a C. glutamicum wild-type strain has not been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…However, C. glutamicum, which is used for production of amino acids, organic acids and alcohols, does not harbor transhydrogenase genes. Recently, the introduction of transhydrogenase genes into C. glutamicum cells has been examined in an attempt to improve production of amino acids and alcohol (Bartek et al, 2011;Blombach et al, 2011;Kabus et al, 2007). However, the effect of transhydrogenases on cellular metabolism in a C. glutamicum wild-type strain has not been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Corynebacterium glutamicum engineered for isobutanol formation indicated a cycle consisting of pyruvate and/or phosphoenolpyruvate carboxylase, malate dehydrogenase, and malic enzyme provided conversion of NADH + H + to NADPH + H + , aided synthesis [55]. Engineering C. glutamicum for valine production by removing pyruvate dehydrogenase activity enhanced flux through the pentose phosphate pathway providing additional NADPH while adding E. coli PntAB decreased the pentose phosphate pathway flux [56].…”
Section: Cofactor Considerations In Metabolic Engineeringmentioning
confidence: 99%
“…6) Alternatively, and like many aerobic and facultative anaerobic bacteria, C. glutamicum is also capable of producing organic acids under anaerobic conditions. Using wild-type or recombinant strains, organic acids such as succinate and lactate have been reported to be produced in significant amounts, [7][8][9][10] but also alcohols such as ethanol 11) and isobutanol, 12) under oxygen-depleted conditions. In C. glutamicum, a metabolic switch that takes place during the transition from aerobic to anaerobic conditions has been documented.…”
mentioning
confidence: 99%